Digital electronics - Salina Muhamad 1980-; Muhammad Nazir Mohammed Khalid (Oxford Fajar Sdn Bhd, 2013)
Digital Electronics is specially written for students in local intuitions of higher learning pursuing engineering diciplines, such as electronics, electrical engineering, mechatronics, telecommunication and computer science. Designed in line with the relevant syllabus of the Ministry of Higher Education, this book presents the basic theories of digital circuits and thier application towards digital systems in an easy-to-understand and straightfoward manner.